PELESTARIAN BUDAYA DAYAK DALAM ARSITEKTUR MASA KINI PADA PERANCANGAN KANTOR GUBERNUR DI KALIMANTAN - Ronald, Gerry; S. Sombu, Alwin (Jurnal Riset Arsitektur, 2022)
Abstract - Currently the architectural phenomenon in Central Borneo is focused on the design of the building and the government used the architecture of the Betang House. Langgam is like a model or style of traditional house for the people of Kalimantan has been known with long houses, because of its elongated shape. The real utility of Langgam Betang for government buildings at this time, it’s only to preserve the original form of the Betang house, which is solely without considering the meaning contained in it. Intention of this research has to revealed the all relation between the building and the meaning contained. Thus the application of the traditional concept of Betang is expected to not diverge from the original. Specifically; this research traces of the traditional architecture of the Betang House. The method that is used in this research is using the method of interpretation of the relation of the building tradition, with the designed and of the construction structure Betang house. This research is using the mix of building anatomy principles with the cultural traditions. The conclusion of this research is about the comprehension the essence of traditional architecture in traditional Betang House, which is based on local custom, thus this typology can be guide in designing the government office building. Keywords: traditional architecture, house Betang, preservation architecture.